2009
DOI: 10.1371/journal.pone.0008072
|View full text |Cite
|
Sign up to set email alerts
|

Systems-Level Comparison of Host-Responses Elicited by Avian H5N1 and Seasonal H1N1 Influenza Viruses in Primary Human Macrophages

Abstract: Human disease caused by highly pathogenic avian influenza (HPAI) H5N1 can lead to a rapidly progressive viral pneumonia leading to acute respiratory distress syndrome. There is increasing evidence from clinical, animal models and in vitro data, which suggests a role for virus-induced cytokine dysregulation in contributing to the pathogenesis of human H5N1 disease. The key target cells for the virus in the lung are the alveolar epithelium and alveolar macrophages, and we have shown that, compared to seasonal hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
109
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 45 publications
10
109
2
1
Order By: Relevance
“…Mem71 is a type A influenza strain of intermediate virulence that, given at sublethal dosages, induces a lung inflammatory response that peaks at day 3 and is resolved by day 10 (34). In contrast, infection with high-fatality influenza A strains (i.e., avian H5N1/97) leads to patient death from acute respiratory distress and multiple organ dysfunction, postulated to be caused by aberrant cytokine production from virus-exposed lung MFs (5,35). Interestingly, CCR2 2/2 mice infected with the highly virulent PR8 influenza A strain virus have decreased lung monocyte recruitment and are protected against morbidity and mortality independent of virus clearance efficiency (6,14), clearly highlighting the significant contributions of lung monocytes in acute lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…Mem71 is a type A influenza strain of intermediate virulence that, given at sublethal dosages, induces a lung inflammatory response that peaks at day 3 and is resolved by day 10 (34). In contrast, infection with high-fatality influenza A strains (i.e., avian H5N1/97) leads to patient death from acute respiratory distress and multiple organ dysfunction, postulated to be caused by aberrant cytokine production from virus-exposed lung MFs (5,35). Interestingly, CCR2 2/2 mice infected with the highly virulent PR8 influenza A strain virus have decreased lung monocyte recruitment and are protected against morbidity and mortality independent of virus clearance efficiency (6,14), clearly highlighting the significant contributions of lung monocytes in acute lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with evidence that macrophages support productive replication of some IAV strains, excessive cytokine production following H5N1 infection may be a result of productive virus replication in macrophages. Of particular interest because of its role in immunopathology, the cytokine TNF-a is induced to high levels in human MDMs infected with HPAI H5N1 viruses or with a seasonal H3N2 virus [16,52,59]. While these studies did not directly correlate TNF-a production with virus replication, in another report, HPAI H5N1 and seasonal H3N2 IAV were shown to replicate in human MDMs [37].…”
Section: Iav Replication and Hypercytokinemiamentioning
confidence: 96%
“…On the other hand, macrophages have been implicated in the pathogenesis of severe IAV disease. Excessive pulmonary infiltration of macrophages secreting enhanced levels of pro-inflammatory cytokines is a hallmark of IAVinduced severe pneumonia [14][15][16][17]. Recently, efforts to understand the role of macrophages in IAV pathogenesis have focused on whether influenza viruses have the ability to replicate productively in macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…We next investigated whether the expression of cytokines typically up-regulated following influenza A virus infection (Fig. 4A) (14,15) is TLR10 dependent. TLR10 shRNA knockdown (KD) in THP-1 cells (Fig.…”
Section: Tlr10 Is Expressed In Human Macrophages and Its Expression Ismentioning
confidence: 99%
“…Our previous studies have demonstrated that influenza A virus replicates and induces proinflammatory cytokine responses and paracrine cytokine cascades in human peripheral blood monocyte-derived macrophages and alveolar epithelial cells (13)(14)(15).…”
mentioning
confidence: 99%